Orchids and their conservation at Natural History Museum, Kathmandu, Nepal - Shrestha, Keshab (Journal of Natural History Museum, 2008)
Though small in area, Nepal is considered to be rich in orchid flora. It has been realized that archid flora in Nepal has not been fully explored. Orchid in gardens, green houses and even in home decoration is not fully well appreciated due to difficulty in its assemblage, lack of knowledge in culture and garden varieties. Natural History Museum, Kathmandu has tried to accumulate some orchid species in its garden and in herbarium, attempting to create awareness for its conservation. In the present paper orchid of less attraction for garden development has been described from its collection. Some of such species are Eulophia dabia, Gastrochilus acutifolius, Coelogyne flavida, Cleisostoma filiforme, Vanda testacea, Dendrobium bicameratum and so on. If a well-established method is developed for their survival in the garden, it can be said that such orchid species can well be popularized and can be conserved forever. J. Nat. Hist. Mus. Vol.22, 2005 p.57-63